Islam and the Western Philosophy of Knowledge - Ibrahim M. Abu-Rabi' (International Institute of Islamic Thought, 1997)
It is a simple truism to state that any scholar who treats such a vast topic as "Islam and the Western Philosophy of Knowledge" must be familiar with the different domains of intellectual and philosophical discourses in bvth the Muslim and the western worlds, their epistemological bases (i.e., foundational conceputal principles), historical evolution, and cultural expressions. In addition, such a scholar cannot do justice to this imponant topic without constructing an appropriate and comprehensive comparative method that might shed some light on why there have been some important divergences between the Muslim worldview and the western one, especially in the modern period (e.g., the past few centuries). Third, in dealing with the above subject, a scholar must know at least one Islamic language (e.g., Arabic) and one European language in addition to English (e.g., French or German). Measured against this criteria, the author of this (very) tiny work fails miserably to justify his goal(s) for writing this book, to offer a convincing method of comparative analysis, and to prove that he possesses the appropiate tools (i.e., sources and languages) with which to conduct his research. To begin with, the author states in the Preface that he intends to offer "a humble contribution to the contemporary debate on the need for a new epistemology.” The nature of the contemporary debate the author refers to is unclear: Is it an Islamic debate? Western or African? Second, what is the nature of this new epistemology of which he speaks? His entire discussion throughout the book does not mention any new epistemology per se, but rather a historically old and established one: that of the Qur’an and other revelations. So, is the author offering a Qur’anic rationale for and justification of some uiucial philosophical issues arising in the modem westem world, or is he interested in measuring the impact of western philosophy on the modem Muslim mind in the context of colonialism and the new world order? No such desire is expressed. When the author states in his Acknowledgment that “I came to the conclusion that the real malaise of the Muslim Umma is the intellectual,” he does not tell us why it is so and why it is not economic, political, social, or a combination of the abov ...